Problem of Information Security Traffic on Internet - Šarić, Slavko; Peraković, Dragan; Bara, Danijel (Promet - Traffic&Transportation)
Internet information traffic becomes greater and moreimportant. With increasing growth of information importancerequirement for its security becomes indispensable. Theinformation security problem especially affect large and smallcompanies whose prosperity is depending on Internet presence.This affecting the three areas of Internet commerce: credit cardtransactions, virtual private networks and digital certification.To ensure information traffic it is necessary to find a solution,in a proper way, for three major problems: frontier problem,market problem and government problem. While the eventualemergence of security standards for Internet transactions isexpected, it will not automatically result in secure Internettransactions. In future, there is a wealth of security issues thatwill continue to require attention: internal security, continuedhacking, social engineering, malicious code, reliability andperformance, skills shortages and denial of se1vice attacks.